A fluorescent pH probe for acidic organelles in living cells. Issue 37 (13th September 2017) - Chen, Jyun-Wei; Chen, Chih-Ming; Chang, Cheng-Chung
Abstract : The molecular design of pH sensor ADA is based on combining photoinduced electron transfer (PET) and intramolecular charge transfer (ICT). The fluorescent emission response against a pH value is suitable for probing acidic organelles in living cells. Abstract : A water-soluble pH sensor, 2-(6-(4-aminostyryl)-1, 3-dioxo-1 H -benzo[ de ]isoquinolin-2(3 H )-yl)- N, N -dimethylethanamine (ADA), was synthesized based on the molecular design of photoinduced electron transfer (PET) and intramolecular charge transfer (ICT). The fluorescence emission response against a pH value is in the range 3–6, which is suitable for labelling intracellular pH-dependent microenvironments. After biological evolution, ADA is more than a pH biosensor because it is also an endocytosis pathway tracking biosensor that labels endosomes, late endosomes, and lysosome pH gradients. From this, the emissive aggregates of ADA and protonated-ADA in these organs were evaluated to explore how this probe stresses emission colour change to cause these unique cellular images.